An Improved Gas-Kinetic Scheme for Multimaterial Flows (Communications in Computational Physics, 2020)
The efficiency of recently developed gas-kinetic scheme for multimaterialflows is increased through the adoption of a new iteration method in the kinetic non-mixing Riemann solver and an interface sharpening reconstruction method at a cellinterface. The iteration method is used to determine the velocity of fluid interface,based on the force balance between both sides due to the incidence and bounce backof particles at the interface. An improved Aitken method is proposed with a simplehybrid of the modified Aitken method (Aitken-Chen) and the Steffensen method. Numerical tests validate its efficiency with significantly less calls to the function not onlyfor the average number but also for the maximum. The new reconstruction is basedon the tangent of hyperbola for interface capturing (THINC) but applied only to thevolume fraction, which is very simple to be implemented under the stratified framework and capable of resolving fluid interface in mixture. Furthermore, the directionalsplitting is adopted rather than the previous quasi-one-dimensional method. Typicalnumerical tests, including several water-gas shock tube flows, and the shock-watercylinder interaction flow show that the improved gas-kinetic scheme can capture fluidinterfaces much sharper, while preserving the advantages of the original one.